4, 4′-Bipyridine-based Ni(ii)-metallogel for fabricating a photo-responsive Schottky barrier diode device. (11th August 2021) - Das, Pubali; Majumdar, Santanu; Dey, Arka; Mandal, Sourav; Mondal, Atish; Chakrabarty, Sinchan; Ray, Partha Pratim; Dey, Biswajit
Abstract : 4, 4′-Bipyridine-based Ni(ii )-metallogel has been implemented to execute a light-responsive semiconducting Schottky barrier diode device with advanced functionality. Abstract : A functionally advanced Ni(ii )-metallogel (Ni-D-TA) was prepared through the sonication of nickel(ii ) chloride hexahydrate and 4, 4′-dipyridyl and triethyl amine in an N, N -dimethyl formamide solvent at room temperature under ambient conditions. The rheological investigation proves the mechanical stability of the functional Ni-D-TA metallogel. FESEM microstructural analysis unveils a rock-like morphology with a self-assembled architecture of the Ni-D-TA metallogel. The optical and electrical properties of the metallogel were thoroughly examined, and the results indicate the semiconducting nature of Ni-D-TA. Electrical conductivity and photosensitivity show its capability in optoelectronic device application. Also, it is seen from the experimental studies that light irradiation endows the metallogel with better device parameters and charge transport properties. The rectification ratio increases to two-fold under illumination. This type of metallogel with photosensing Schottky behaviour advances the area of optoelectronic devices.